Les manuscrits de l’abbé de Castries dans la collection Gaignières : une donation exceptionnelle ? - Sarah Héquette (Les Cahiers de l'École du Louvre)
On 21 October 1709, Armand-Pierre de La Croix de Castries gave a hundred or so manuscripts to the famous antiquarian François-Roger de Gaignières. Thanks to an inventory written in the latter’s hand, we now have knowledge of this gift, as exceptional as it is eclectic. A little-known figure, the Abbé de Castries, originally from the Languedoc, worked alongside Parisian scholars. As for Gaignières, a renowned collector of the reign of Louis XIV, he built up a collection of more than 5,000 items, including nearly 1,100 manuscripts, and thus preserved the memory of the elites of the medieval and modern eras. In this article, we will look back at the constitution and composition of the batch of manuscripts, and also attempt to understand what led the Abbé de Castries to make the donation and what it contributed to the Gaignières collection.